2009
DOI: 10.1128/aac.00645-08
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Salmonella enterica Serovar Typhi IncHI1 Plasmids during the Global Spread of Resistant Typhoid Fever

Abstract: A global collection of plasmids of the IncHI1 incompatibility group from Salmonella enterica serovar Typhi were analyzed by using a combination of DNA sequencing, DNA sequence analysis, PCR, and microarrays. The IncHI1 resistance plasmids of serovar Typhi display a backbone of conserved gene content and arrangement, within which are embedded preferred acquisition sites for horizontal DNA transfer events. The variable regions appear to be preferred acquisition sites for DNA, most likely through composite transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 46 publications
4
91
0
Order By: Relevance
“…However, it might be more commonly the case than anticipated that S. Typhi haplotype H58B harbors the IncHI1 plasmid or chromosomally translocated antimicrobial resistance islands or both. It has been hypothesized that a milestone of IncHI1 plasmid evolution had been reached around 1996 by the acquisition of increased fitness, with the result that the IncHI1 plasmid has outcompeted all other plasmid types in S. Typhi (44). However, it has also been argued that plasmid fitness cost must play a role in maintaining IncHI1 plasmids in S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…However, it might be more commonly the case than anticipated that S. Typhi haplotype H58B harbors the IncHI1 plasmid or chromosomally translocated antimicrobial resistance islands or both. It has been hypothesized that a milestone of IncHI1 plasmid evolution had been reached around 1996 by the acquisition of increased fitness, with the result that the IncHI1 plasmid has outcompeted all other plasmid types in S. Typhi (44). However, it has also been argued that plasmid fitness cost must play a role in maintaining IncHI1 plasmids in S. Typhi.…”
Section: Discussionmentioning
confidence: 99%
“…The chromosomal haplotypes of S. Typhi isolates were determined based on the SNPs present at 1,485 chromosomal loci identified previously (11,27; see also Table S1 and the methods in the supplemental material). These and eight IncHI1 plasmid loci identified previously (25) were investigated using a GoldenGate custom panel according to the manufacturer's standard protocols (Illumina) (see the methods in the supplemental material). A maximum-likelihood phylogenetic tree based on chromosomal SNPs was constructed using RAxML software (29).…”
Section: Methodsmentioning
confidence: 99%
“…However, this monophyletic (clonal) pathogen presents particular challenges in this regard. Studies on the population structure of S. Typhi have shown that this human-adapted pathogen exhibits extremely limited genetic variation, challenging our ability to develop discriminatory tools of value in the field (3,11,25,27). However, the application of novel deep-sequencing and bioinformatics approaches has succeeded in stratifying the S. Typhi population into distinct phylogenetic lineages based on over 1,000 single-nucleotide polymorphisms (SNPs) distributed throughout the chromosome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(Garcia-Fernandez et al, 2009;Literak et al, 2009;Moodley and Guardabassi, 2009) 2. (Garcia-Fernandez et al, 2008;Phan et al, 2009;Villa et al, 2010) …”
Section: Detection and Classification Of Plasmids Carrying Esbl And/omentioning
confidence: 99%